A Political Patronage and Its Impact on Service Delivery in Uganda: Kabale Municipality, Kabale District - Mugabe, Robert; Adyanga, Francis Akena; Ocan, Johnson (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
abstract This study seeks to undertake a thorough analysis of the effects of political patronage, a pervasive and deeply rooted practice that is prevalent throughout Uganda and has profound implications for governance and service delivery. In this research, Kabale Municipality, located in Kabale District, serves as a crucial case study. This municipality has been selected due to its unique political dynamics and the evident discrepancies in service delivery that reflect broader national trends. By exploring the disparities in service provision between regions that are considered loyal to the government and those that maintain affiliations with opposition parties, this study aims to provide a comprehensive understanding of how political patronage shapes the landscape of service delivery in Uganda. The situation in Kabale is illustrative of the systemic issues prevalent across the country, making it an ideal microcosm for this analysis. The research employs a comparative case study design that is intricately guided by the philosophical framework of critical realism. A diverse range of qualitative methodologies, including in-depth interviews, focus group discussions, and direct observational studies. The expected recommendations may include the introduction of policy reforms that enhance transparency and accountability in the allocation of resources, the establishment of more inclusive and participatory mechanisms for decision-making, and the implementation of strategies designed to empower marginalized communities that have historically been sidelined due to their political affiliations. Key words: political patronage, service delivery, participatory politics, decision making